Computer Systems Architecture : A Networking Approach - Williams, Rob. (Harlow : Hall, 2006)
Intended for students of Computer Science or Engineering, this title aims to lay the foundations for more detailed courses on Networking. It provides a description of ARM and Itanium processors and an introduction to the field of data communications. It also offers coverage of MPEG algorithms for audio and video compression in portable devic
Keywords: Computer Architecture; Computer Network Architectures